Insufficiency fracture of the tibial plateau In rheumatoid arthritis - Vidal Neira, Luis (1992)
The ocurrence of insufficiency fractures in patients with long-standing, rheumatoid arthritis has not been sufficiently emphasized.  Osteoporosis due to rheumatoid arthritis, corticosteroid therapy, contracture and angular deformity of the extremity, combine to predispose to the ocurrence of the insufficiency fractures in these patients. Additionally, the pain and disability caused by the fracture is often attributed to rheumatoid joint involvement, masking the diagnosis of insufficiency fracture. The fracture may not be visible on radiographs near the onset of symptoms, and the bone scanning can help in make an early diagnosis.